From Secondary School to University: Associations Between Domain-Specific Sedentary Behaviors and Lifestyle Risk Behaviors - Ignasi Arumi-Prat PhD; Eva Cirera PhD; Jim McKenna PhD; Anna Maria Puig-Ribera PhD (SAGE Publishing, 2022)
This study examined associations between changes in domain-specific sedentary behaviors and changes in health-related lifestyles of Spanish secondary school students (n = 113) to their first year of university. During the transitions from the end of high school to the beginning of university, engagement in sedentary behaviors have emerged as potential additional behavioral risk factors. Understanding how sedentary behaviors interconnect with other (un)healthy behaviors will inform interventions on multiple risk behaviors across this critical life period. A 3-year longitudinal survey assessed associations between domain-specific sedentary behaviors and leisure time physical activity (IPAQ), alcohol and tobacco consumption, and fruit and vegetable intake (24-h dietary recall), using Generalized Estimating Equations. Spending time on sedentary transportation was associated with a greater likelihood of smoking, whereas sedentary weekend homework was associated with a reduced likelihood of consuming alcohol. The lowest and highest tertiles for sedentary screen use and leisure-time PA were also less likely not to meet the recommendations for fruit and vegetable consumption. For specific sedentary behaviors, associations were gender-based or affected by leisure time physical activity. From secondary school to university, specific sedentary behaviors are linked to lifestyle risk factors. Over this transitional period, public health interventions targeting reduced sedentary behaviors may bring multiple benefits by also preventing other harmful behaviors.